From plurinational electoral reform to intercultural democracy in Bolivia: The case of the Mosetén people - Díaz-Villanueva, Augusto (2024)
This article discusses the progress, in normative and democratization terms, of the mechanisms and dynamics of the political participation system of the Indigenous peasant peoples of Bolivia. The objective of such discussion is to represent the functioning of the institutional assemblage of the Departmental Legislative Assembly of La Paz and the uses and customs of the Indigenous Mosetén people. For this analysis, it is understood that the Plurinational State has been the result of a process of state construction in which the Indigenous peasant peoples have struggled for representation and recognition. In this article, a systematic analysis is carried out of the institutional innovations introduced through the Plurinational State, which have entailed electoral reform. The paradigm of intercultural democracy is discussed and operationalized through the notion of assemblage, as this case is approached through its characterization and through interviews of key actors. It is concluded that the mechanisms introduced in Bolivia open paths to recognize other, non-liberal democracies and that the inclusion of historically excluded ethnic minorities is possible. However, the obstacles and challenges faced by Indigenous populations to consolidate what is described in the law are also illustrated.